Anthropocentric by Default? Attribution of Familiar and Novel Properties to Living Things. (8th May 2017) - Arenson, Melanie; Coley, John D.
Abstract: Humans naturally and effortlessly use a set of cognitive tools to reason about biological entities and phenomena. Two such tools, essentialist thinking and teleological thinking, appear to be early developmental cognitive defaults, used extensively in childhood and under limited circumstances in adulthood, but prone to reemerge under time pressure or cognitive load. We examine the nature of another such tool: anthropocentric thinking. In four experiments, we examined patterns of property attribution to a wide range of living and non‐living objects, manipulating time pressure, response type, and property (either novel or familiar) in a total of 471 participants. Results showed no tendency toward increased similarity‐based attribution patterns indicative of anthropocentric thinking under time pressure. However, anthropocentric thinking was consistently observed for unfamiliar properties. These findings suggest that anthropocentric thinking is not a developmentally persistent cognitive default, but rather a cognitive strategy deliberately employed in situations of uncertainty.